Long-term outcome after pancreas transplantation: a registry analysis. Issue 4 (August 2016) - Gruessner, Angelika C.; Gruessner, Rainer W.G.
Abstract : Purpose of review: Pancreas transplantation provides the only proven method to restore long-term normoglycemia in patients with insulin-dependent diabetes mellitus. Although many studies describe the most important risk factors for short-term survival of a pancreas transplant, more information about factors that distinguish short-term from long-term graft function is needed. Recent findings: Analysis of 21 328 pancreas transplants from the International Pancreas Transplant Registry, performed from 1984 to 2009 (minimum 5-year follow-up), shows a significant improvement in long-term patient survival and pancreas graft function. Total 5-and 10-year pancreas graft function rates are 73 and 56%, respectively, for simultaneous pancreas–kidney transplants; 64 and 38%, respectively, for pancreas after kidney; and 53 and 36%, respectively, for pancreas transplants alone. The most influential period is the first year posttransplant. Recipients who reach this time point with a functioning graft have a much higher probability for excellent long-term graft function. Important factors influencing long-term function were features that described the quality of the deceased donor. Pancreas transplants in younger, high panel reactive antibody, or African-American recipients also showed an increased risk of early graft failure. Anti-T-cell induction therapy had a significant impact on long-term survival in solitary transplants. Summary: With careful recipient and donor selection and close follow-up in the first year posttransplant, not only good short-term but also long-term pancreas graft function and, therefore, durable metabolic control can be achieved for the diabetic patient.